Assessment of nutritional status among adolescents: a hospital based cross sectional study - Singh, J. P.; Kariwal, Peeyush; Gupta, S. B.; Singh, Atul Kumar; Imtiaz, Danish (International Journal of Research in Medical Sciences, 2017)
Background:Adolescence, a period of transition between childhood and adulthood, occupies a crucial position in the life of human beings. The primary causes of under nutrition in India are its large population, socio-economic differences and inadequate access to health facilities. Nutritional assessments among adolescents are important as they are the future parents and constitute a potentially susceptible group. Studies on the assessment of nutritional status of adolescents are less in number and a National database has not yet been developed. Methods:The present hospital based cross sectional study was conducted in year 2013 among 344 rural adolescents of 10-19 years age (166 boys and 178 girls) attending the outpatient department at rural health training centre (RHTC) Dhaura Tanda, district Bareilly, Uttar Pradesh, belonging to the Muslim and Hindu caste communities. The nutritional status was assessed in terms of under nutrition (weight-for-age below 3rd percentile), stunting (Height-for-age below 3rd percentile) and thinness (BMI-for-age below 5th percentile). Diseases were accepted as such as diagnosed by pediatrician, skin specialist and medical officer. Results:The prevalence of underweight, stunting and thinness were found to be 32.8%, 19.5% and 26.7% respectively. The maximum prevalence of malnutrition was observed among early adolescents (28%-47%) and the most common morbidities were URTI (38.6%), diarrhea (16.8%), carbuncle / furuncle (16%) and scabies (9.30%). Conclusion:The study concluded that the most common morbidities among adolescents were related to nutrition and personal hygiene. Regular health programmes should focus to educate and promote health among adolescent.